Factors influencing consumers’ willingness to accept service robots: Based on online reviews of Chinese hotels - Chang, Cheng; Shao, Bingjia; Li, Yong; Zhang, Yong (Frontiers in Psychology, 2022)
The application of robots in service industry is increasing. Compared with related studies in other countries, the research on users' acceptance of middle- and high-class hotel service robots in China is preliminary. Based on the interaction between Chinese consumers and hotel service robots, this study explored the factors that influence consumers' willingness to accept robots in human-robot interaction. According to the service robot integration willingness scale (performance efficacy, intrinsic motivation, anthropomorphism, social influence, facilitating conditions, emotion), this study made content analysis and sentiment analysis on 4107 online reviews from sixty-eight middle- and high-class hotels in Qunar. The results showed that users' overall evaluation of robot service in middle- and high-class hotels is positive. The most frequently mentioned dimension by users is performance efficacy, followed by intrinsic motivation, anthropomorphism, and emotion, finally, the facilitating conditions, the five dimensions have positive impact on users' evaluation of service robots; the influence of social influence on human-robot interaction evaluation has not been found. This study supplements the research on service robot and provides a reference for hotel managers to make decisions.